NbN superconducting nanonetwork fabricated using porous silicon templates and high-resolution electron beam lithography. (20th October 2017) - Salvato, M; Baghdadi, R; Cirillo, C; Prischepa, S L; Dolgiy, A L; Bondarenko, V P; Lombardi, F; Attanasio, C
Abstract: Superconducting NbN nanonetworks with a very small number of interconnected nanowires, with diameter of the order of 4 nm, are fabricated combining a bottom-up (use of porous silicon nanotemplates) with a top-down technique (high-resolution electron beam lithography). The method is easy to control and allows the fabrication of devices, on a robust support, with electrical properties close to a one-dimensional superconductor that can be used fruitfully for novel applications.